PERCEPTUAL MAP TEACHING STRATEGY - Chipoco, Mario (2016)
This paper comprises the design of a strategy to teach perceptual mapping in a Brand Management course, adding a modeling technique in order to elaborate such maps. Perceptual maps are tools used to analyze the positioning of a brand, and are taught in undergraduate and graduate courses. However, very frequently a purely descriptive and theoretical framework is used, disregarding the mechanisms to construct them. Methods based on multiple linear regression and factorial analysis are presented as modeling tools to explain and foster a better understanding of this subject in class.